2019
DOI: 10.1175/bams-d-18-0033.1
|View full text |Cite
|
Sign up to set email alerts
|

On Bridging A Modeling Scale Gap: Mesoscale to Microscale Coupling for Wind Energy

Abstract: Accurately representing flow across the mesoscale to the microscale is a persistent roadblock for completing realistic microscale simulations. The science challenges that must be addressed to coupling at these scales include the following: 1) What is necessary to capture the variability of the mesoscale flow, and how do we avoid generating spurious rolls within the terra incognita between the scales? 2) Which methods effectively couple the mesoscale to the microscale and capture the correct nonstationary featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 46 publications
0
46
0
Order By: Relevance
“…As a consequence, care must be taken to consider any gradients in the velocity field caused by mesoscale effects (as discussed by e.g. Haupt et al 2019). When mesoscale https://doi.org/10.5194/wes-2020-62 Preprint.…”
Section: Description Of the Multiple Transfer Location Analysis (Mtla)mentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, care must be taken to consider any gradients in the velocity field caused by mesoscale effects (as discussed by e.g. Haupt et al 2019). When mesoscale https://doi.org/10.5194/wes-2020-62 Preprint.…”
Section: Description Of the Multiple Transfer Location Analysis (Mtla)mentioning
confidence: 99%
“…The microscale effects have also been modelled by coupling WRF with a large variety of non-linear CFD models (eg. Gopalan et al 2014, Haupt et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, advances in computational power and new modeling capabilities have led several WRF user groups to experiment with simulations at higher spatial resolutions [3][4][5][6]. While increased model resolution has the potential to improve simulation performance, it can also complicate the task of turbulence modeling and lead to inaccurate outcomes, especially at horizontal resolutions between the meso and microscales, a modeling region known as the "terra incognita" or "gray zone" [7,8]. At these resolutions, the subgrid-scale (SGS) model lies between the fully parameterized regime, where the mesoscale approach based on horizontal homogeneity across the grid footprint is applicable and the large-eddy simulation (LES) regime, where small isotropic eddies are parameterized according to Kolmogorov's theory.…”
Section: Introductionmentioning
confidence: 99%
“…Another practical resolution and hitherto accuracy limit of NWP models results from the use of parameterizations itself. Using WRF, Haupt et al (2019) observed that for horizontal grid spacings below the typical height of the PBL numerical results can become spurious. Based on their findings, they recommend not to apply NWP on the sub-kilometer scale without careful replacement of the used parameterizations.…”
Section: Introductionmentioning
confidence: 99%
“…LES models resolve the turbulent spectra up to the filter cut-off size (often the grid size) and rely on simplistic sub-scale parameterizations only (Maronga et al, 2019). These two different approaches (extensive parameterization vs. explicit representation) are difficult to merge at the bridging scale-range (few tens of meters to one kilometer), for which reason Haupt et al (2019) introduced the key word "terra-incognita". An exemplary study where LES have been attempted at horizontal resolutions up to above 100 m is given by Efstathiou et al (2016).…”
Section: Introductionmentioning
confidence: 99%